Measurement of Physicochemical Properties, Electrical and Thermal Conductivity of Wood Ash for Effective Soil Amendment - M O Kanu; Gabriel Wirdzelii Joseph; Israel George (Department of Physics, Sebelas Maret University, 2021)
The ability of the soil to regulate heat energy is important for plant growth, soil texture and strength. Many agricultural soils are acidic in nature which tends to limit plant growth and microbial activity. Aside from agricultural lime, wood ash is used to amend physical and physicochemical properties of the soil. To maintain the soil hydraulic and physicochemical properties and to increase plant yield, it is important to know the physicochemical and physical properties of the ash used. The physiochemical and physical properties vary across various plant species. Ash samples from seven different plants were used for this study. The Horiba metre was used to measure the electrical conductivity, pH, Total Dissolved Solid (TDS) and salinity of the samples, while the Lees Disc apparatus was used to measure the thermal conductivity of the samples. The study revealed that moringa olieferra ash has the highest salinity, TDS and Electrical conductivity, while azadichta indica and tiobroma cacoa have least pH. Also, Kyah seleelygalisis and azadichta indica had the highest and lowest thermal conductivity respectively.